Peran Digitalisasi Layanan Pelanggan dalam Memperkuat Loyalitas di Industri E-Commerce - Fajar, Arfi; Sundari, Pipit (STIE Semarang, 2024)
Customer service digitization has become a crucial factor in enhancing the competitiveness of the e-commerce industry. This study aims to explore the role of customer service digitization in strengthening consumer loyalty in the e-commerce industry. Using a qualitative approach, this study examines the implementation of digitalization strategies through case studies and in-depth interviews with experts in the e-commerce industry. The results show that customer service digitization, including the use of chatbots, data-driven personalization, and omnichannel integration, plays a significant role in improving customer experience. This, in turn, has a positive impact on customer loyalty. This finding is supported by the analysis of recent literature which shows that consumers increasingly prioritize convenience, speed, and responsiveness in interacting with e-commerce platforms. In addition, this study identifies several challenges faced by e-commerce companies in implementing customer service digitization, such as the need for significant technology investment and the need for ongoing employee training. In conclusion, customer service digitization not only improves operational efficiency but also plays a key role in building long-term customer loyalty in the e-commerce industry. This study provides in-depth insights for e-commerce industry players and researchers interested in digital transformation strategies.